Bahasa Inggris - Burhani, Ahmad Furqon; Ika Prajawati, Maretha (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to determine the effect of profitability and liquidity moderated by firm size on health sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 - 2022. The sample in this study was determined using purposive sampling technique and obtained 11 sample companies that met the criteria, so there were 55 total financial reports. Multiple linear regression analysis or applied to data testing. The results of this study indicate that profitability and firm size have a positive effect on firm value, while liquidity has no effect on firm value. The role of firm size in moderation is only able to moderate the relationship between profitability and firm value. Meanwhile, firm size cannot moderate the relationship between liquidity and firm value.